GO modified composite metal compound photocatalyst as well as preparation method and application thereof
By modifying the composite metal compound on the surface of graphene oxide to form a nanocomposite photocatalyst, the problems of high production cost, poor stability and high-temperature reaction in the prior art are solved, and the low-cost and efficient photocatalytic decomposition of N2O is achieved.
Patent Information
- Application Number
- CN202411469024.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-25
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a photocatalyst for photocatalyzing N2O, and in particular to a graphene oxide (GO) modified composite metal compound photocatalyst and a preparation method and application thereof. Background Art
[0002] Since the 21st century, countries have been constantly discussing and proposing strategies around climate change, environmental pollution, biodiversity and other issues, but have not fundamentally solved the problem. N2O (commonly known as laughing gas) is a gas that is seriously harmful to the environment and human health. Compared with CO2 and CH4 greenhouse gases, N2O can stay in the atmosphere for about 150 years. Although the concentration of N2O in the atmosphere is much lower than CO2, N2O's ability to absorb infrared radiation is about 310 times that of CO2, and its contribution to the greenhouse effect is about 6-10%. The increase in the concentration of greenhouse gases such as N2O will seriously damage the balance of the ecosystem. The problem of global warming will affect the sustainable development of human society and the ecological environment system on which humans depend for survival. As an important source of atmospheric greenhouse gases, N2O has increasingly attracted widespread attention from scientists and climatologists in various countries. Effective governance, elimination or mitigation of the impact of N2O, measures and technologies have far-reaching economic and social benefits. Studies have shown that catalytic decomposition is the most promising N2O removal technology, in which catalysts are the core of the process and have become one of the hot spots in the field of research in this technology. Research on N2O decomposition catalysts is currently focused on the research of catalytic materials related to the thermal catalytic decomposition of N2O. However, the thermal catalytic decomposition of N2O requires the reaction system to be heated to a certain temperature before the catalytic decomposition of N2O can be achieved. The N2O decomposition reaction is a highly exothermic reaction, which has relatively high requirements for equipment materials. Photocatalysis is a green technology that uses solar energy to degrade pollutants. Photocatalysis can be carried out at room temperature, saving energy; and it can completely decompose atmospheric pollutants into harmless substances without causing secondary pollution. It is widely used because of its high efficiency, convenience and pollution-free nature. Among the many common oxide photocatalysts, TiO2 has the widest application range. However, the wide band gap of TiO2, about 3.2 eV, leads to its low utilization rate of visible light. In addition, defects such as the high recombination rate of photogenerated electron-hole pairs limit the expanded application of TiO2 (“Hydrogen production using TiO2-based photocatalysts: A comprehensive review”, ACS Omega, 2023, 8(29): 25640-25648; “Progress in photothermal catalytic materials for CO2 reduction”, New Chemical Materials, 2023, http: / / kns.cnki.net / kcms / detail / 11.2357.TQ.20230719.0946.003.html).
[0003] CN106994341B discloses a composite oxide catalyst for photocatalytic decomposition of N2O, the general formula of which is Bi m X 1 0.2-3 X 2 0-3 O n , where X 1 Selected from elements W, X 2 Selected from element Fe or Co, the composite metal oxide is prepared by hydrothermal synthesis. Due to the difference in the physicochemical properties of the metal oxide precursors, the reaction conditions have a great influence on the photocatalytic performance of the prepared composite metal oxide. CN113797749B discloses a photocatalytic NO degradation catalyst using TiCl4 as a precursor and synthesizing TiO2 loaded with Mn by hydrothermal method. Since TiCl4 is easily formed into TiO2 when in contact with water, the prepared TiO2 particles have a small specific surface area. Therefore, the existing photocatalysts for photocatalytic decomposition of N2O have problems. Summary of the invention
[0004] In view of the above technical problems, the present invention provides a graphene oxide modified composite metal compound photocatalyst and its preparation method and application, which solves the shortcomings of high manufacturing cost and poor catalyst stability of the thermal catalytic decomposition of N2O catalyst in the prior art. At the same time, the photocatalytic reaction is carried out under conditions close to the ambient temperature, which solves the shortcomings of thermal catalytic decomposition under high temperature conditions and strict requirements on equipment materials. Compared with thermal catalytic decomposition reaction, photocatalytic decomposition has outstanding advantages such as simple operation, low energy consumption, low operating cost, and no secondary pollution.
[0005] To achieve the above object, the technical solution of the present invention is:
[0006] A graphene oxide modified composite metal compound photocatalyst comprises a nano composite metal compound loaded on the surface of graphene oxide and interacting with active groups on the surface of the graphene oxide, wherein the composite metal compound comprises a transition metal oxide and a filtering metal sulfide.
[0007] Graphene oxide has a large specific surface area and oxygen-rich active groups. The nanocomposite metal compound is loaded on the surface of the graphene oxide, and the nanocomposite metal compound interacts with the graphene oxide group. The transition metal oxide modifies the graphene oxide surface, which helps to highly disperse the nanocomposite metal compound and inhibits the aggregation of high specific surface area GO. The GO-modified composite metal compound catalyst provided, on the one hand, takes advantage of the composite photocatalyst that can utilize light energy at multiple energy levels, and at the same time, the graphene oxide surface is conducive to the adsorption of nitrogen oxide molecules on the catalyst surface, increasing the active sites of the catalytic reaction, and is conducive to the catalytic decomposition of N2O.
[0008] Preferably, the mass ratio of the transition metal oxide to the transition metal sulfide is (0.5-2.0):1.0, and the content of graphene oxide in the composite metal compound is (0.001-1.0) wt.%.
[0009] The transition metal oxide in the composite metal compound may be the root of the photocatalytic effect in the photocatalyst, while the transition metal sulfide may play a role in the photocatalytic effect, such as improving the activity and selectivity of the photocatalyst and improving the stability, anti-toxicity, mechanical strength, life span, etc. Therefore, a ratio lower than 0.5:1 or higher than 2.0:1 will affect the performance of the photocatalyst, and the synergistic effect of the composite photocatalyst of the transition metal oxide and sulfide cannot be exerted.
[0010] Preferably, the transition metal oxide includes oxides of Bi, Ti, Fe, W, Zn, Cu and Sn.
[0011] Bi can not only promote light absorption, but also effectively promote the migration of photogenerated charges, thereby improving photocatalytic activity; Fe oxide can make the valence band and conduction band of the prepared photocatalytic material more diffuse, which is conducive to the migration of photogenerated electron-hole pairs, thereby enhancing photocatalytic activity; ZnO has good photocatalytic performance under certain conditions combined with suitable preparation methods, and can effectively use visible light to convert light energy into chemical energy for the degradation of pollutants in the atmosphere; The biggest feature of W photocatalyst is its safety and non-toxicity, and its broad-spectrum characteristics make W photocatalyst have significant effects on a variety of inorganic and organic pollutants. At the same time, the theoretical life of W photocatalyst is infinite, which further ensures the feasibility of long-term use of photocatalyst; Cu photocatalyst has good electron transfer ability and catalytic activity, can effectively promote the energy transfer and chemical reaction of photosensitizer, and Cu photocatalyst has the characteristics of low cost, non-toxicity, environmental protection, and high efficiency; Sn-based photocatalysts are gradually being used in the field of photocatalysis due to their efficient photocatalytic degradation ability, responsiveness to visible light, high redox ability, good photocatalytic performance and high stability. Titanium dioxide (TiO2) is one of the most commonly used photocatalytic materials, has good photochemical properties, can effectively convert visible light energy into chemical energy, and eliminate environmental problems caused by air pollutants. Therefore, in the present invention, oxide composite metal compounds of Bi, Ti, Fe, W, Zn, Cu and Sn are selected.
[0012] Preferably, the transition metal sulfide includes sulfides of Cd, Zn, Mo and the like.
[0013] Sulfides such as CdS, ZnS and MoS2 are representative materials in the application of photocatalysis. They have adjustable band structures. When these semiconductor materials change from multilayer to single layer, their bandgap width will become wider, resulting in changes in optical and electrical properties. However, the photocatalytic performance of these materials is not high, mainly because their photogenerated charge ability is relatively low. In order to improve the photocatalytic performance of these materials, a composite method is adopted, that is, these sulfides are composited with other photocatalysts such as TiO2, etc., so as to obtain a composite semiconductor photocatalyst with better performance. CdS is further preferred. CdS has good visible light response, high catalytic efficiency, stable performance, no toxic side effects, and no secondary pollution. Therefore, CdS, an environmentally friendly catalytic material, is preferred.
[0014] Based on the same inventive concept, the present invention also provides a method for preparing the graphene oxide modified composite metal compound photocatalyst, comprising the following steps:
[0015] S1: Preparation of composite metal compounds by precipitation method;
[0016] S2: Preparation of graphene oxide modified composite metal compounds by hydrothermal method.
[0017] The step S1 specifically includes:
[0018] S101: dissolving a transition metal organic salt in an organic solvent, dissolving a soluble metal salt in deionized water, dissolving an inorganic sulfide salt in deionized water, or dissolving an inorganic sulfide gas in deionized water;
[0019] S102: under stirring and 60-90° C., respectively, adding an inorganic sulfide salt solution or a solution formed by inorganic sulfide gas and a transition metal organic salt solution to a soluble metal salt solution, stirring and reacting for 0.5-4 h, standing, filtering, washing, and drying the precipitate obtained by filtration in a drying oven under an inert atmosphere;
[0020] S103: The product dried in step S102 is placed in a high-temperature furnace in an inert gas atmosphere and calcined to remove organic solvents or impurities in the solid matter, and the temperature is increased to 450° C. at a heating rate of 4° C. / min and kept at this temperature for 4 hours to obtain a composite metal compound.
[0021] Preferably, the concentration of the soluble metal salt solution is 0.01-1.0M, preferably 0.03-0.5M, the concentration of the inorganic sulfide salt solution is 0.01-3.0M, preferably 0.05-1.0M, and the concentration of the metal organic salt solution is 0.001-0.5M.
[0022] Preferably, the transition metal organic salt is selected from: tetrabutyl titanate (TBOT), tetraethyl titanate (TEOT) or tetraisopropyl titanate (TIPT); the above-mentioned tetrabutyl titanate (TBOT), tetraethyl titanate (TEOT) and tetraisopropyl titanate (TIPT) and other organic metal salts are selected as precursors of titanium oxide, and the hydrolysis method is used to prepare TiO2, which makes it easier to control its particle size and structure, so that the composite photocatalyst has better photocatalytic performance.
[0023] The organic solvent is selected from: methanol, ethanol, isopropanol, n-propanol or butanol;
[0024] The soluble metal salt is selected from nitrate or sulfate, and the inorganic sulfide salt is selected from sodium sulfide or potassium sulfide; the inorganic sulfide gas is a hydrogen sulfide gas mixture, and the H2S concentration is 0.5-20 (v)%, preferably 1.0-5.0 (v)%.
[0025] Preferably, step S2 specifically includes:
[0026] S201: dissolving the composite metal compound and graphene oxide prepared in step S: in ethanol, and then placing the mixed solution in a high-pressure reactor, reacting at a temperature of 120-180° C. for 2-10 hours, filtering and washing after the reaction, and drying the filtered precipitate in a drying oven in an inert atmosphere;
[0027] S202: The product dried in step S201 is placed in a high-temperature furnace in an inert gas atmosphere for calcination to remove impurities in the solid powder, and the temperature is increased to 200-700° C. at a heating rate of 2-8° C. / min, and kept at this temperature for 2-6 hours to obtain a composite metal oxide modified with graphene oxide.
[0028] In the preparation method of the present invention, the composite metal compound reacts with graphene oxide in a reactor, so that the nano-composite metal oxide is loaded on the surface of the graphene oxide, and the nano-composite metal oxide interacts with the active groups on the graphene oxide to prepare a photocatalyst with a synergistic effect.
[0029] Preferably, the concentration of the graphene oxide solution is 0.01-1.0 mM, preferably 0.05-2.0 mM.
[0030] Inert gases include nitrogen, argon and helium, preferably argon.
[0031] Based on the same inventive concept, the present invention also provides an application of the graphene oxide modified composite metal compound photocatalyst for photocatalytic decomposition of N2O.
[0032] The light source used for photocatalytic decomposition is ultraviolet light or visible light.
[0033] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art:
[0034] The graphene oxide composite transition metal compound provided by the present invention is used as a catalyst for photocatalytic decomposition of N2O. Compared with the metal compound monomer catalyst, the composite photocatalyst can utilize light energy at multiple energy levels to improve the catalytic efficiency of the catalyst; at the same time, the graphene oxide surface is conducive to the adsorption of nitrogen oxide molecules on the catalyst surface, increasing the active sites of the catalytic reaction, which is conducive to the catalytic decomposition of N2O.
[0035] The photocatalytic decomposition of N2O provided by the present invention is carried out at a temperature almost close to that of the ambient temperature. Compared with the thermal catalytic decomposition reaction, the photocatalytic decomposition has the outstanding advantages of simple operation, low energy consumption, low running cost, and no secondary pollution. It is a truly environmentally friendly green technology. DETAILED DESCRIPTION
[0036] The following is a further detailed description of a graphene oxide modified composite metal compound photocatalyst and its preparation method and application proposed by the present invention in conjunction with specific embodiments. The advantages and features of the present invention will become clearer according to the following description.
[0037] The GO (graphite) used in the following examples was prepared from natural graphite powder by a modified Hummers method ("Preparation of graphitic oxide", Journal of the American Chemical Society, 1958, 80(6): 1339-1339). The prepared GO was dispersed in an ethanol solution at a concentration of 0.1 mM for later use.
[0038] Example 1
[0039] S1: Weigh 11.506g CdSO4·8 / 3H2O and 10.005g Na2S respectively and dissolve them in 250mL and 15mL deionized water, stir to fully dissolve them, weigh 57.077g tetrabutyl titanate (TBOT) and add it to 300mL ethanol solution, stir to fully dissolve it. Transfer the CdSO4·8 / 3H2O solution into a four-necked flask, and then transfer the Na2S solution and TBOT solution into a constant pressure funnel respectively, under the conditions of 70℃ constant temperature water bath, reflux and stirring, add the Na2S solution and organic titanium salt solution dropwise in parallel, and complete the addition within 50 minutes. After the addition is completed, continue to stir at constant temperature for 40 minutes, transfer the flocculated mixture solution into a stainless steel hydrothermal crystallization kettle, stand and age for 6 hours at 85℃, filter the precipitate, and wash it with deionized water three times. The filtered precipitate was dried in an oven at 105°C for 16 hours and then calcined in a muffle furnace using a programmed temperature method. The programmed temperature calcination process was from room temperature to 450°C at a rate of 4°C / min and kept warm for 4 hours. Both drying and calcination were carried out under argon protection to obtain CdS / TiO2 composite metal compound 1.
[0040] S2: The prepared composite metal compound 1 was placed in a beaker and 200 mL of ethanol solution was added, and 10 mL of the prepared 0.1 mM GO solution was measured and added to the above solution. After ultrasonic treatment for 30 minutes, it was placed in a high-pressure reactor with a polytetrafluoroethylene liner, and reacted for 4 hours under argon protection and a temperature of 150°C. After the reaction was completed, it was filtered and washed with deionized water and ethanol respectively. The filtered precipitate was dried in an oven at 105°C for 16 hours, and then calcined in a muffle furnace using a programmed temperature rising method. The programmed temperature rising calcination process was from room temperature to 300°C at a rate of 2°C / min, and kept warm for 4 hours. Both drying and calcination were carried out under argon protection to obtain GO-modified CdS / TiO2 composite metal compounds.
[0041] Comparative Example 1
[0042] The method of step S1 of Example 1 was used to prepare a CdS / TiO2 composite metal compound not modified by GO.
[0043] Example 2
[0044] S1: Weigh 10.514g CdSO4·8 / 3H2O and 9.892g Na2S respectively and dissolve them in 250mL and 15mL deionized water, stir to fully dissolve them, weigh 39.251g tetraethyl titanate (TEOT) and add it to 250mL ethanol solution, stir to fully dissolve it. First, transfer the CdSO4·8 / 3H2O solution into a four-necked flask, transfer the Na2S solution and TEOT solution into a constant pressure funnel respectively, and add the metal salt aqueous solution and the organic titanium salt solution dropwise in a 70℃ constant temperature water bath, reflux and stirring conditions, and complete the addition within 40 minutes. After the addition is completed, continue to stir at a constant temperature for 30 minutes, transfer the flocculated mixture solution into a stainless steel hydrothermal crystallization kettle, and let it stand for 4 hours at 90℃, filter the precipitate, and wash it with deionized water three times. The filtered precipitate was dried in an oven at 105°C for 12 hours and then calcined in a muffle furnace using a programmed temperature method. The programmed temperature calcination process was from room temperature to 450°C at a rate of 4°C / min and kept warm for 4 hours. Both drying and calcination were carried out under argon protection to obtain CdS / TiO2 composite metal compound 2.
[0045] S2: The prepared composite metal compound 2 was placed in a beaker and 200 mL of ethanol solution was added, and 10 mL of the prepared 0.1 mM GO solution was measured and added to the above solution. After ultrasonic treatment for 30 minutes, it was placed in a high-pressure reactor with a polytetrafluoroethylene liner. Under argon protection and a temperature of 150°C, the reaction was carried out for 6 hours. After the reaction was completed, it was filtered and washed with deionized water and ethanol respectively. The filtered precipitate was dried in an oven at 105°C for 16 hours, and then calcined in a muffle furnace using a programmed temperature rising method. The programmed temperature rising calcination process was from room temperature to 300°C at a rate of 2°C / min, and kept warm for 4 hours. Both drying and calcination were carried out under argon protection to obtain GO-modified CdS / TiO2 composite metal compounds.
[0046] Comparative Example 2
[0047] The method of step S1 of Example 2 was used to prepare a CdS / TiO2 composite metal compound that was not modified by GO.
[0048] Example 3
[0049] S1: Weigh 10.098g CdSO4·8 / 3H2O and 9.798g Na2S respectively and dissolve them in 250mL and 15mL deionized water, stir to fully dissolve them, weigh 47.656g tetraisopropyl titanate (TIPT) and add it to 250mL ethanol solution, stir to fully dissolve it. First, transfer the CdSO4·8 / 3H2O solution into a four-necked flask, transfer the Na2S solution and TIPT solution into a constant pressure funnel respectively, and add the metal salt aqueous solution and the organic titanium salt solution dropwise in a 70℃ constant temperature water bath, reflux and stirring conditions, and complete the addition within 30 minutes. After the addition is completed, continue to stir at a constant temperature for 30 minutes, transfer the flocculated mixture solution into a stainless steel hydrothermal crystallization kettle, and let it stand for 8 hours at 90℃, filter the precipitate, and wash it with deionized water three times. The filtered precipitate was dried in an oven at 105°C for 20 hours and then calcined in a muffle furnace using a programmed temperature method. The programmed temperature calcination process was from room temperature to 450°C at a rate of 4°C / min and kept warm for 4 hours. Both drying and calcination were carried out under argon protection to obtain a CdS / TiO2 composite metal compound.
[0050] S2: The prepared composite metal compound was placed in a beaker and 200 mL of ethanol solution was added, and 10 mL of the prepared 0.1 mM GO solution was measured and added to the above solution. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-pressure reactor with a polytetrafluoroethylene liner. The mixture was reacted for 8 hours under argon protection and a temperature of 140°C. After the reaction was completed, the mixture was filtered and washed with deionized water and ethanol respectively. The filtered precipitate was dried in an oven at 105°C for 16 hours, and then calcined in a muffle furnace using a programmed temperature increase method. The programmed temperature increase calcination process was performed by heating the room temperature from 2°C / min to 300°C and keeping the temperature for 4 hours. Both drying and calcination were carried out under argon protection to obtain a GO-modified CdS / TiO2 composite metal compound.
[0051] Comparative Example 3
[0052] The method of step S1 of Example 3 was used to prepare a CdS / TiO2 composite metal compound that was not modified by GO.
[0053] Comparative Example 4
[0054] S1: Weigh 12.120g CdSO4·8 / 3H2O and 10.098g Na2S respectively and dissolve them in 250mL and 15mL deionized water, stirring to fully dissolve. First, transfer the CdSO4·8 / 3H2O solution into a three-necked flask, transfer the Na2S solution into a constant pressure funnel, add the Na2S aqueous solution dropwise in a 70℃ constant temperature water bath, reflux and stirring conditions, and complete the addition within 20 to 30 minutes. After the addition is completed, continue to stir at a constant temperature for 20 to 30 minutes, transfer the flocculated mixture solution into a stainless steel hydrothermal crystallization kettle, and let it stand for 8 hours at 90℃. Filter the precipitate and wash it with deionized water three times. The filtered precipitate was dried in an oven at 105°C for 20 hours and then calcined in a muffle furnace using a programmed temperature method. The programmed temperature calcination process was from room temperature to 450°C at a rate of 4°C / min and kept warm for 4 hours. Both drying and calcination were carried out under argon protection to obtain a CdS2 compound.
[0055] S2: The prepared CdS2 compound was added with 160 mL of ethanol solution, and 8 mL of the prepared 0.1 mM GO solution was added to the above solution. After ultrasonic treatment for 30 minutes, it was placed in a high-pressure reactor with a polytetrafluoroethylene liner. Under argon protection and a temperature of 140°C, the reaction was carried out for 8 hours. After the reaction was completed, it was filtered and washed with deionized water and ethanol respectively. The filtered precipitate was dried in an oven at 105°C for 16 hours, and then calcined in a muffle furnace using a programmed temperature rising method. The programmed temperature rising calcination process was from room temperature to 300°C at a rate of 2°C / min, and kept warm for 4 hours. Both drying and calcination were carried out under argon protection to obtain a GO-modified CdS compound.
[0056] Comparative Example 5
[0057] S1: Weigh 46.835g of tetraisopropyl titanate (TIPT) and add it to 150mL of ethanol solution, stir to fully dissolve it, and prepare 200mL of ethanol solution with a mass concentration of 15%. First, transfer the ethanol solution into a three-necked flask, transfer the TIPT solution into a constant pressure funnel, and add the TIPT solution to the ethanol solution under 70℃ constant temperature water bath, reflux and stirring conditions. The addition is completed within 20 to 30 minutes. After the addition is completed, continue to stir at constant temperature for 30 minutes. The flocculated mixture solution is transferred into a stainless steel hydrothermal crystallization kettle, and is allowed to stand and age for 8 hours at 90℃. The precipitate is filtered and washed with deionized water three times. After the filtered precipitate is dried in a 105℃ oven for 20 hours, it is calcined in a muffle furnace using a programmed temperature method. The programmed temperature calcination process is to heat the room temperature from 4℃ / min to 450℃, and keep warm for 4 hours. The drying and calcination are carried out under argon protection to obtain TiO2 compound.
[0058] S2: The prepared TiO2 compound was placed in a beaker and 200 mL of ethanol solution was added, and 9 mL of the prepared 0.1 mM GO solution was measured and added to the above solution. After ultrasonic treatment for 30 minutes, it was placed in a high-pressure reactor with a polytetrafluoroethylene liner. Under argon protection and a temperature of 140°C, the reaction was carried out for 8 hours. After the reaction was completed, it was filtered and washed with deionized water and ethanol respectively. The filtered precipitate was dried in an oven at 105°C for 16 hours, and then calcined in a muffle furnace using a programmed temperature rising method. The programmed temperature rising calcination process was from room temperature to 300°C at a rate of 2°C / min, and kept warm for 4 hours. Both drying and calcination were carried out under argon protection to obtain a GO-modified TiO2 compound.
[0059] Evaluation and analysis methods of photocatalytic decomposition of N2O
[0060] The performance of the prepared composite material in catalytic decomposition of N2O was evaluated by using a heat-resistant and pressure-resistant photoreactor with gas internal circulation. The reactor volume was 300mL. 5g of the 40-60 mesh composite metal compound prepared in the embodiment and the comparative example was weighed and placed in the reactor. Visible light with a wavelength of 250-950nm was used as the light source. The reaction gas mixture was prepared in advance. The composition (volume percentage) of the mixed gas was 9.85% N2O+15.23% O2+N2 (balance gas), and the system pressure was 0.2MPa. After the gas mixture containing N2O reacted in the reactor for a certain period of time, the concentration of N2O in the gas mixture before and after the reaction was analyzed by an online SP-3420 gas chromatograph (chromatographic column Paropak Q, TCD detector), and the conversion rate of N2O was calculated. The results are shown in Table 1.
[0061] Table 1 Changes in the conversion rate of catalytic decomposition of N2O under light conditions
[0062]
[0063] From the comparison of Examples 1-3 and Comparative Examples 1-3 in Table 1, it can be seen that the catalyst of the present invention has catalytic activity for decomposing N2O under light irradiation conditions, and the activity of the catalyst for catalytic decomposition of N2O is significantly improved by using GO to modify the composite metal oxide. It can be seen that the catalyst of the present invention has excellent performance in photocatalytic decomposition of N2O.
[0064] By comparing Examples 1-3 with Comparative Examples 4-5, it can be seen that the activity of the catalysts in the examples in catalyzing the decomposition of N2O is significantly higher than that in Comparative Examples 4-5, indicating that the activity of the photocatalytic decomposition of N2O by using GO-modified composite metal oxides is significantly higher than that by using GO-modified transition metal oxides or sulfides, further indicating that the transition metal oxides and sulfides in the composite metal oxides of the present invention have a synergistic effect.
[0065] The above is a detailed description of the implementation of the present invention in conjunction with specific embodiments, but the present invention is not limited to the above implementation. Even if various changes are made to the present invention, if these changes fall within the scope of the claims of the present invention and their equivalents, they still fall within the protection scope of the present invention.
Claims
1. A graphene oxide modified composite metal compound photocatalyst, characterized in that: The invention comprises a nano composite metal compound supported on the surface of graphene oxide and interacting with active groups on the surface of the graphene oxide, wherein the composite metal compound comprises a transition metal oxide and a filtering metal sulfide.
2. The graphene oxide modified composite metal compound photocatalyst according to claim 1, characterized in that: The mass ratio of the transition metal oxide to the transition metal sulfide is (0.5-2.0):1.0, and the content of graphene oxide in the composite metal compound is (0.001-1.0) wt.%.
3. The graphene oxide modified composite metal compound photocatalyst according to claim 1, characterized in that: The transition metal oxides include oxides of Bi, Ti, Fe, W, Zn, Cu and Sn.
4. The graphene oxide modified composite metal compound photocatalyst according to claim 1, characterized in that: The transition metal sulfides include sulfides of Cd, Zn and Mo.
5. A method for preparing a graphene oxide modified composite metal compound photocatalyst according to any one of claims 1 to 4, characterized in that: The steps include: S1: preparing a composite metal compound; S2: Preparation of graphene oxide modified composite metal compounds by hydrothermal method.
6. The method for preparing the graphene oxide modified composite metal compound photocatalyst according to claim 5, characterized in that: The step S1 specifically includes: S101: dissolving a transition metal organic salt in an organic solvent, and dissolving a soluble metal salt in deionized water; S102: under stirring and 60-90° C., respectively, adding an inorganic sulfide salt solution or a solution formed by inorganic sulfide gas and a transition metal organic salt solution dropwise to a soluble metal salt solution, continuing to stir and react for 0.5-4 h, standing, and then filtering, washing, and drying; S103: placing the product dried in step S102 in a high-temperature furnace in an inert gas atmosphere, heating the temperature to 450° C. at a heating rate of 4° C. / min, and keeping the temperature for 4 hours to obtain a composite metal oxide.
7. The method for preparing the graphene oxide modified composite metal compound photocatalyst according to claim 6, characterized in that: The concentration of the soluble metal salt solution is 0.01-1.0M, the concentration of the inorganic sulfide salt solution is 0.01-3.0M, and the concentration of the metal organic salt solution is 0.001-0.5M.
8. The method for preparing the graphene oxide modified composite metal compound photocatalyst according to claim 6, characterized in that: The transition metal organic salt is selected from: tetrabutyl titanate, tetraethyl titanate or tetraisopropyl titanate; the organic solvent is selected from: methanol, ethanol, isopropanol, n-propanol or butanol; The soluble metal salt is selected from nitrate or sulfate, the inorganic sulfide salt is selected from sodium sulfide or potassium sulfide; and the inorganic sulfide gas is a hydrogen sulfide gas mixture.
9. The method for preparing the graphene oxide modified composite metal compound photocatalyst according to claim 5, characterized in that: Step S2 specifically includes: S201: dissolving the composite metal compound and graphene oxide prepared in step S: in ethanol, and then placing the mixed solution prepared above in a high-pressure reactor, reacting at a temperature of 120-180° C. for 2-10 hours, and filtering, washing, and drying after the reaction is completed; S202: placing the product dried in step S201 in a high-temperature furnace in an inert gas atmosphere, heating the temperature to 200-700° C. at a heating rate of 2-8° C. / min, and keeping the temperature for 2-6 hours to obtain a graphene oxide-modified composite metal compound.
10. An application of the graphene oxide modified composite metal compound photocatalyst according to any one of claims 1 to 4, characterized in that: Used for photocatalytic decomposition of N2O.
Citation Information
Patent Citations
Catalysts for photocatalytic decomposition of N2O, their preparation methods and applications
CN106994341B